Marine-Lenhart Syndrome: Current Perspectives on Diagnosis and Management - Alexander Kam; Yanne Pradwi Efendi; Dinda Aprilia; Eva Decroli; Syafril Syahbuddin; Suci Berlian Hemilton (CV. AKBAR PUTRA MANDIRI, 2025)
Marine-Lenhart syndrome (MLS) is an uncommon disorder characterised by the concurrent presence of Graves’ disease and hyperfunctioning thyroid nodules. Its global prevalence ranges between 2.7- 4.1% of Graves’ disease cases, presenting significant challenges in diagnosis and management. MLS is often difficult to detect due to limitations in autoimmune serology tests, thyroid ultrasonography, and access to nuclear medicine facilities. Diagnosis relies on a combination of clinical hyperthyroidism symptoms, the presence of specific thyroid antibodies, and scintigraphy findings that reveal